2016
DOI: 10.5194/acp-16-7195-2016
|View full text |Cite
|
Sign up to set email alerts
|

Sources of organic ice nucleating particles in soils

Abstract: Abstract. Soil organic matter (SOM) may be a significant source of atmospheric ice nucleating particles (INPs), especially of those active > −15 • C. However, due to both a lack of investigations and the complexity of the SOM itself, the identities of these INPs remain unknown. To more comprehensively characterize organic INPs we tested locally representative soils in Wyoming and Colorado for total organic By contrast, lysozyme, which digests bacterial cell walls, only reduced INPs active at ≥ −7.5 or ≥ −6 • C… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
250
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 184 publications
(285 citation statements)
references
References 88 publications
(110 reference statements)
18
250
0
Order By: Relevance
“…Even amongst standard immersion freezing methods, uncertainties of a factor of a few n INPs (T ) and 2-4 • C are likely common on the basis of this study and may be the best that can be achieved. Application of size selection to immersion freezing collections for comparison to MOUDI-DFT data (especially at lower temperatures) and CFDC data; information on INP compositions inferred under all sampling scenarios to help constrain influences of various types (e.g., methods of Hill et al, 2016); and an intercomparison of all methods vs. a cloud parcel simulation chamber, considered as a de facto standard, would all assist resolution and improvement of understanding of measurement discrepancies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even amongst standard immersion freezing methods, uncertainties of a factor of a few n INPs (T ) and 2-4 • C are likely common on the basis of this study and may be the best that can be achieved. Application of size selection to immersion freezing collections for comparison to MOUDI-DFT data (especially at lower temperatures) and CFDC data; information on INP compositions inferred under all sampling scenarios to help constrain influences of various types (e.g., methods of Hill et al, 2016); and an intercomparison of all methods vs. a cloud parcel simulation chamber, considered as a de facto standard, would all assist resolution and improvement of understanding of measurement discrepancies.…”
Section: Discussionmentioning
confidence: 99%
“…2.2) were also cooled, and correction for any frozen aliquots in the pure water control vs. temperature was made in all cases, similar to the CS method. Binomial sampling confidence intervals (95 %) were determined for IS data, as described in Hill et al (2016).…”
Section: Colorado State University Ismentioning
confidence: 99%
“…This temperature was chosen because some biological materials have been shown to lose their ice nucleation activity following heating to 95 • C (Christner et al, 2008), possibly due to denaturation of the tertiary structure of ice nucleating proteins (Hill et al, 2016). Samples of microlayer and bulk seawater were put into polypropylene tubes, sealed with lids, and heated to 100 • C in a heating block (Accublock, Labnet, S/N: D1200) for an hour, then cooled to room temperature for approximately 30 min before freezing measurements.…”
Section: Heating Testsmentioning
confidence: 99%
“…This results in a significant impact on the extent, lifetime, formation of precipitation and radiative properties of clouds . Currently, four mechanisms are proposed for heterogeneous ice nucleation in mixed-phase clouds: deposition ice nucleation, condensation freezing, immersion freezing and contact freezing (Vali et al, 2015;Hoose and Möhler, 2012). It is under discussion whether condensation freezing is different from immersion freezing on a fundamental level (Wex et al, 2014) and whether at least some of the observed deposition ice nucleation can be attributed to pore condensation and freezing (Marcolli, 2014).…”
Section: Introductionmentioning
confidence: 99%